Cariprazine in the treatment of Bipolar Disorder: A systematic review and meta‐analysis. (19th November 2019) - Pinto, Jairo Vinícius; Saraf, Gayatri; Vigo, Daniel; Keramatian, Kamyar; Chakrabarty, Trisha; Yatham, Lakshmi N.
Abstract: Objectives: Cariprazine is a partial agonist at D2/D3 receptors that has been approved for the treatment of mania associated with bipolar disorder (BD). This meta‐analysis aimed to assess the efficacy and tolerability of cariprazine in the treatment of BD. Methods: Randomized controlled trials investigating the efficacy of cariprazine in BD were included. Of the 391 studies yielded by search, 7 were included. The PRISMA protocol was followed and a set of analyses involving random‐effects model with restricted maximum‐likelihood estimator were used to synthesize effect sizes. Results: Cariprazine was associated with a moderate and significant reduction of manic symptoms based on YMRS change scores (SMD: −0.52; 95%CI: −0.82 to −0.21; P  = .018). Cariprazine resulted in significantly higher remission (OR: 2.05; 95%CI: 1.61‐2.61; P  = .006) and response rates (OR: 2.31; 95%CI: 1.35‐3.95; P  = .021) for manic and mixed episodes compared with placebo. Both cariprazine 1.5 mg and 3 mg doses were associated with small but significant reduction in depressive symptoms assessed with MADRS scores (SMD: −0.26, 95%CI: −0.49 to −0.02; P  = .040) (SMD: −0.21, 95%CI: −0.41 to −0.01; P  = .045), respectively. Cariprazine was significantly associated with the development of adverse effects but not with dropouts due to these adverse effects, when compared to placebo. Conclusion: Cariprazine appears to be safe and efficacious in the treatment of acute mania and mixed episodes associated with BD. Cariprazine at doses of 1.5‐3 mg/day is efficacious in acute bipolar depression but the effect sizes were smaller. Controlled studies evaluating its efficacy for prophylaxis are needed.